2007
DOI: 10.1590/s0100-83582007000100019
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância do milheto (Pennisetum americanum) ao 2, 4-D

Abstract: , CARGNELUTTI FILHO, A. 4 e SILVA, I.S. 5RESUMO -Objetivou-se com este trabalho avaliar os efeitos do 2,4-D sobre o crescimento das plantas, a produção de massa seca e verde e a produtividade de grãos do milheto. O experimento foi realizado no período de março a junho de 2006, em Rio Verde-GO, em um Latossolo Vermelho eutroférrico. O milheto (cultivar ADR 500) foi semeado manualmente em área cultivada sob sistema de plantio direto, em espaçamento de 0,45 m, distribuindo-se 12 sementes por metro. Utilizou-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
11
Order By: Relevance
“…Apesar de ser uma espécie que vem ganhando destaque na região dos cerrados, não existe no mercado brasileiro nenhum herbicida registrado para uso na cultura do milheto (Pereira Filho et al, 2003). Controle flexível e eficiente de espécies latifoliadas tem sido obtido com atrazine (Ndahi et al, 1980), 2,4-D (Farinelli et al, 2005Pacheco et al, 2007) e carfentrazone-ethyl (Lyon et al, 2007); contudo, opções para o controle de gramíneas na cultura do milheto ainda não foram identificadas.…”
Section: Introductionunclassified
“…Apesar de ser uma espécie que vem ganhando destaque na região dos cerrados, não existe no mercado brasileiro nenhum herbicida registrado para uso na cultura do milheto (Pereira Filho et al, 2003). Controle flexível e eficiente de espécies latifoliadas tem sido obtido com atrazine (Ndahi et al, 1980), 2,4-D (Farinelli et al, 2005Pacheco et al, 2007) e carfentrazone-ethyl (Lyon et al, 2007); contudo, opções para o controle de gramíneas na cultura do milheto ainda não foram identificadas.…”
Section: Introductionunclassified
“…The selectivity of atrazine to corn plants is due to herbicide degradation (Vidal 2001), so that the used dose was probably high to plant support the effect of the herbicide, in spite of being a recommended dose. In addition, 2,4-D can cause negative impact on corn plants (Pacheco et al 2007, Dan et al 2010, depending on the used dose, in spite of 1A 1B…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dicamba applied at 280 g ae ha −1 had little or no effect on crop height, only a slight increase by 6% compared to the control being noted at Rocky Mount in 2012 and Kinston in 2014 when dicamba was applied on 45 or 55 cm tall sorghum. Other studies have reported nonsignificant decrease in plant height with 2,4-D applied at 335, 670, or 1005 g ae ha −1 and on three-to six-leaf stage grain sorghum [12] whereas significant reduction occurred at the same 2,4-D rates on three-leaf stage pearl millet [Pennisetum americanum (L.) Leeke] [24]. These contrasting results may be due to differential sensitivity to 2,4-D, which is associated with genetic variations of the different sorghum cultivars.…”
Section: Crop Height At Bootmentioning
confidence: 99%